Influence Analysis Number of Blue and Red Light Emitting Diode (LED) Variation on Soybean (Glycine Max) Growth - Wilda Prihasty; Intan Dwi Kurniawati; Iman Ramacaesar Rosohadi; Achmad Syarif Hidayat; Selvy Uftovia Hepriyadi (Institut Teknologi Sepuluh Nopember, 2018)
Soybean (Glycine Max) is one of the agricultural commodities that still had particularly low production rate on a national scale in Indonesia. Despite the demand for the soybean it’s increasing along with the population growth in Indonesia. Thus, the need of soybean which mainly as main ingredient of tempe and tahu is still filled from importers. These problems can be solved by the research of applying artificial light technology in the agricultural sector so it would help optimize soybean growth. The purpose of this research is determines the effect of Blue Light and Red Light Emitting Diode (LED) lighting on the growth of soybean (Glycine max). Soybeans were grown in uniform boxes that had controlled temperature and humidity with regulated soybean seeds, soil, and planting methods. Based on the results from the research that had been conducted on the growth of the soybean, it is determined that most optimum soybean plant is using the lighting ratio of the red LEDs 75% and blue 25% with a height of 15 cm in the ninth day and the chlorophyll concentration is 52,4265953 mg/l. But plant with sun source lighting is better than using LED, it is about 118,8138334 mg/l. Based on the result that had been obtained, this research can be used as reference in the making of modern artificial light for soybean for research development in agriculture especially on soybean commodity which could support government efforts in suppressing important soybeans and meet domestic soybean demand using national production.